A multiple case study on the effects of location and target market of a lifestyle retail store in its interior design - Cuaresma, Czarinamie A. (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT This study sought to evaluate and compare the design of three chosen branches of a local lifestyle retail store and find out how the interior design of each branch is influenced by two significant factors namely, its location and its target market. Using purposive selection, the branches of the local lifestyle retail store that were examined are located at different malls within Metro Manila and target different markets namely, Metropoint Mall, which caters mainly to the lower market, Trinoma Mall, which caters to the middle class market, and Power Plant which caters to the upper class market. An observation guide and photo documentation tools were used to carry out the objectives of this research. The results of the study show that the interior design was modified in each branch of the local lifestyle retail store to appeal to the palate of its target market. There were recognizable differences in the materials, treatments and maintenance among the three store branches. The study revealed that the higher the market the store targets, the more expensive the materials are utilized for the store, the more design treatments are allotted to it and also, the more attention to maintenance is given to it. Based on the results of the research, this study can help designers and retailers alike in designing retail stores that are appropriate for their target market. Thus, providing retail stores more opportunity to maximize their market potential. This study, however did not consider the effect of the interior design of each of the branch on consumers and therefore recommends that a follow up research must be done on how design in different locations with different target market is able to affect customers and their buying behavior in the Filipino setting.